2020
DOI: 10.15407/ubj92.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and hypolipidemic effects of Corchorus olitorius leaves as a food supplement on rats with alloxan-induced diabet

Abstract: Corchorus olitorius is a species of shrub in the family malvaceae known to have rich sources of chemical compounds. the leaves of this plant are locally consumed as a vegetable and as a remedy in Africa, middle east and Southern Asia. this study was designed to evaluate the hypoglycemic and hypolipidemic effects of C. olitorius leaves sample given for 14 days as a food supplement to rats with alloxan-induced diabetes. Twenty one male albino rats weighing 150-200 g were randomly assigned into three groups: 1-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…A study by Olusanya et al ( 34 ) confirmed the anti-diabetic properties of C. olitorius in a rodent model of T2D. Interestingly, other studies have also shown a beneficial effect of C. olitorius on glucose and lipid level profiles in the same model animal of T2D ( 35 , 36 ). Most recently, Lee and team ( 37 , 38 ) demonstrated the anti-dyslipidemic properties of C. olitorius extract and reduced body weight in rodent models of obesity.…”
Section: Introductionmentioning
confidence: 84%
“…A study by Olusanya et al ( 34 ) confirmed the anti-diabetic properties of C. olitorius in a rodent model of T2D. Interestingly, other studies have also shown a beneficial effect of C. olitorius on glucose and lipid level profiles in the same model animal of T2D ( 35 , 36 ). Most recently, Lee and team ( 37 , 38 ) demonstrated the anti-dyslipidemic properties of C. olitorius extract and reduced body weight in rodent models of obesity.…”
Section: Introductionmentioning
confidence: 84%
“…Plant bers may chelate with intestinal glucose therefore reducing blood glucose levels, in addition they contribute in the reduction of circulating plasma cholesterol because they trap bile in intestine leading to more bile production from cholesterol. 39 Mahgoub et al evaluated the effect of C. olitorius soup (prepared from C. olitorius leaves) on fasting blood glucose, lipid prole, and hepatic oxidative status in STZ-induced diabetes in male albino rats. Treatment with C. olitorius soup (given at a dose of 4.80 g per kg body weight) showed encouraging antihyperglycemic, antihypertriglyceridemic as well as antioxidant properties.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Plant fibers may chelate with intestinal glucose therefore reducing blood glucose levels, in addition they contribute in the reduction of circulating plasma cholesterol because they trap bile in intestine leading to more bile production from cholesterol. 39 …”
Section: Pharmacological Biodiversitymentioning
confidence: 99%